ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI DI PROVINSI BANTEN MENGGUNAKAN REGRESI LINIER DAN GEOGRAPHICALLY WEIGHTED REGRESSION - Arief Rachman Hakim (Jurnal Statistika Universitas Muhammadiyah Semarang, 2020)
Economic growth in a particular area can be measured by the amount of Gross Regional Domestic Product (GRDP). Looking at the geographical location, Banten province is an area directly adjacent to Jakarta where there are many industrial sectors and there are activities in the Sunda Strait port, which is the mainland entrance between the islands of Java and Sumatra, causing economic activity to grow quite well in Banten Province. According to BPS data, economic growth in Banten Province rose by 5.59%. The increase also supports by several sectors there are agriculture, industry business and several other sectors. Linear regression method is a method commonly used to model the correlation of predictor variables and response variables. The weakness of this method is that the model produced is only one and global variable. Geographically Weighted Regression (GWR) is the development of location-weighted linear regression (spatial) based on regional characteristics so that the parameters and variables that influence will also be different for each location. The best model selected by the largest R square (R2) criterion and the smallest Akaike Information Criteria (AIC) value. The AIC value of the Linear Regression model is 47,094 and the AIC GWR value is 54,024, also the R2 GWR is 0.953 while the linear regression R2 is 0.87.